BSACI guideline for the diagnosis and management of pollen food syndrome in the UK. Issue 9 (17th August 2022) - Skypala, Isabel J.; Hunter, Hannah; Krishna, Mamidipudi Thirumala; Rey‐Garcia, Helena; Till, Stephen J.; du Toit, George; Angier, Elizabeth; Baker, Sarah; Stoenchev, Kostadin V.; Luyt, David K.
Abstract: Pollen food syndrome (PFS) is a highly prevalent food allergy affecting pollen‐sensitized children and adults. Sufferers experience allergic symptoms when consuming raw plant foods, due to the homology between the pollen allergens and unstable proteins in these foods. The triggers involved can vary depending on the pollen sensitization, which in turn is affected by geographical location. The British Society of Allergy and Clinical Immunology (BSACI) Standards of Care Committee (SOCC) identified a need to develop a guideline for the diagnosis and management of PFS in the United Kingdom (UK). Guidelines produced by the BSACI use either the GRADE or SIGN methodology; due to a lack of high‐quality evidence these recommendations were formulated using the SIGN guidelines, which is acknowledged to be less robust than the GRADE approach. The correct diagnosis of PFS ensures the avoidance of a misdiagnosis of a primary peanut or tree nut allergy or confusion with another plant food allergy to non‐specific lipid transfer proteins. The characteristic foods involved, and rapid‐onset oropharyngeal symptoms, mean PFS can often be diagnosed from the clinical history alone. However, reactions involving tree nuts, peanuts and soya milk or severe/atypical reactions to fruits and vegetables may require additional diagnostic tests. Management is through the exclusion of known trigger foods, which may appear to be simple, but is highly problematic if coupled with a pre‐existing food allergy or for individuals following a vegetarian/vegan diet. Immunotherapy to pollens is not an effective treatment for PFS, and although oral or sublingual immunotherapy to foods seems more promising, large, controlled studies are needed. The typically mild symptoms of PFS can lead to an erroneous perception that this condition is always easily managed, but severe reactions can occur, and anxiety about the onset of symptoms to new foods can have a profound effect on quality of life. Abstract : Pollen food syndrome (PFS) manifests in children and adults sensitised to birch tree pollen. It classically presents with immediate mild oropharyngeal itching/swelling to raw plant foods. Typical triggers include apples, stone fruits, kiwifruit, carrots, celery, hazelnuts, almonds, walnuts, soya milk and peanuts. A diagnosis can be made when characteristic symptoms are reported to classic PFS trigger foods. Those reporting more severe symptoms, or who also react to cooked or atypical plant foods may require allergy tests and/or onward referral.